2020
DOI: 10.2147/iprp.s274406
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge on Dispensed Medications and Its Determinants Among Patients Attending Outpatient Pharmacy at Chencha Primary Level Hospital, Southwest Ethiopia</p>

Abstract: Background: According to World Health Organization (WHO) drug use indicators manual, the patients' knowledge on dispensed medication is a crucial patient care indicator. There is a dearth of studies about patients' knowledge of dispensed medication at the primary health care facility. The objective of this study was to assess the knowledge of dispensed medication and associated factors among patients attending in the outpatient pharmacy of Chencha primary level hospital, Southwest Ethiopia. Methods: A facility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…The finding of this study revealed that the majority of the patients (79.5%, 96.8%, 86.5%, 79.5%, 77.3%, 64.8%, and 81.0%) recalled the indication, route, frequency, duration, instruction on how to use, proper storage, and the expected therapeutic outcomes of dispensed medication’s, respectively. This finding is in line with studies conducted in Ayder Comprehensive Specialized Hospital (ACSH), Mekelle [ 14 ]; Hiwot Fana Specialized University Hospital (HFSUH), Harar [ 13 ]; Chencha Primary Hospital [ 17 ], and Ambo General Hospital (AGH), Ambo [ 16 ]. This shows that in the aforementioned aspects of drugs, most ambulatory patients had sufficient exit knowledge.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The finding of this study revealed that the majority of the patients (79.5%, 96.8%, 86.5%, 79.5%, 77.3%, 64.8%, and 81.0%) recalled the indication, route, frequency, duration, instruction on how to use, proper storage, and the expected therapeutic outcomes of dispensed medication’s, respectively. This finding is in line with studies conducted in Ayder Comprehensive Specialized Hospital (ACSH), Mekelle [ 14 ]; Hiwot Fana Specialized University Hospital (HFSUH), Harar [ 13 ]; Chencha Primary Hospital [ 17 ], and Ambo General Hospital (AGH), Ambo [ 16 ]. This shows that in the aforementioned aspects of drugs, most ambulatory patients had sufficient exit knowledge.…”
Section: Discussionsupporting
confidence: 89%
“…But, the exit knowledge sufficiency of our respondents is less than the studies conducted in the AGH (55.5%) [ 16 ], ACSH, Mekelle (81%) [ 14 ], Gondar (38.3%) [ 20 ], Federal Harar Police Hospital (FHPH) (38.6%) [ 15 ] and HFSUH, Harar (46%) [ 13 ]. But, it is greater than studies done in Chencha Primary Hospital (13.2%) [ 17 ] and Gambia, Western Africa (16.1%) [ 21 ]. These discrepancies in the exit-knowledge of the participants could be attributed to differences in the calculation of knowledge level, percentage of labeled medications, frequency of pharmacy visit, number of drugs received, educational status of the patients, and study setting.…”
Section: Discussionmentioning
confidence: 80%
“…This research supports the findings of a previous study conducted in Ethiopia. 22 Besides types of dosage forms were significantly associated with rational dispensing indicators as indicator 1, indicator 3 and indicator 5 showed a significant relationship. This research supports the findings of a previous study in Sri Lanka.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the correct knowledge of patients on dispensed medications, this study revealed that most patients recalled correctly the route of administration 97.4%, frequency 94.3%, and dose 93.5% of medications but the lesser proportion of patients knew the storage 51.8% and use precautions 34.2% for medications dispensed. Similarly, studies reported a higher level of patient medication knowledge on the route of administration, dosage, and frequency of administration [ 21 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%